Chemistry of fracture‐filling raised ridges in Yellowknife Bay, Gale Crater: Window into past aqueous activity and habitability on Mars. Issue 11 (26th November 2014) - Léveillé, Richard J.; Bridges, John; Wiens, Roger C.; Mangold, Nicolas; Cousin, Agnes; Lanza, Nina; Forni, Olivier; Ollila, Ann; Grotzinger, John; Clegg, Samuel; Siebach, Kirsten; Berger, Gilles; et al.
Abstract The ChemCam instrument package on the Curiosity rover was used to characterize distinctive raised ridges in the Sheepbed mudstone, Yellowknife Bay formation, Gale Crater. The multilayered, fracture‐filling ridges are more resistant to erosion than the Sheepbed mudstone rock in which they occur. The bulk average composition of the raised ridges is enriched in MgO by 1.2–1.7 times (average of 8.3–11.4 wt %; single‐shot maximum of 17.0 wt %) over that of the mudstone. Al2O3 is anticorrelated with MgO, while Li is somewhat enriched where MgO is highest. Some ridges show a variation in composition with different layers on a submillimeter scale. In particular, the McGrath target shows similar high‐MgO resistant outer layers and a low‐MgO, less resistant inner layer. This is consistent with the interpretation that the raised ridges are isopachous fracture‐filling cements with a stratigraphy that likely reveals changes in fluid composition or depositional conditions over time. Overall, the average composition of the raised ridges is close to that of a Mg‐ and Fe‐rich smectite, or saponite, which may also be the main clay mineral constituent of the host mudstone. These analyses provide evidence of diagenesis and aqueous activity in the early postdepositional history of the Yellowknife Bay formation, consistent with a low salinity to brackish fluid at near‐neutral or slightly alkaline pH. The fluids that circulated through the fractures likely interacted with the Sheepbed mudstone and (or) other stratigraphically adjacent rock units of basaltic composition and leached Mg from them preferentially.